Traditional Medicolore in Badwani District (M.P.) India - Patil, P. S. PatilÂ¹*, Patil M.V.Â²; D. A. (Journal of Phytology, 2011)
The study concerns significant ethnobotanical information of 25 plant species belonging to 25 genera and 19 families traditionally used by the aborigines and rural folks of Badwani district, Of these 21 species are being noted for the first time from Indian region.Â Madhya Pradesh (India) to treat various human diseases such as, impotency, intestinal worms, fever, constipation, ring worms, eczema, hepatitis, menstrual complaints, urinary complaints, migraine stomach-ache, bone fracture, lactation, piles, night blindness, pregnancy and abortion, etc.,This paper highlights traditional uses of plants used by the rural and tribal people. The district is inhabited with tribes viz., Gond, Baiga, Koraku, Bhariaya, Halba, Bhil, Kaul and Pawara. The population of the region is predominantly rural and tribal having considerable knowledge about ambient plant wealth and their traditional utility. The present work is an attempt to collect document and evaluate the ethnomedicinal claims in the areas under study. Key words: Ethnomedicine, Badwani District, Madhya Pradesh <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">P. S. Patil. Traditional Medicolore in Badwani District (M.P.) India. J Phytol 2/12 (2010) 49-53.